The Influence of Compensation and Working Environment on Organizational Commitment and its Implications on Employees’ Performance at PT. Sumber Wahana Musi - Yasir Arafat; Tri Darmawati; Ninin Non Ayu Salmah (Cita Konsultindo Research Center, 2023)
This study aims to determine the effects of compensation and working environment on organizational commitment and its implications on the performance of employees at PT. Sumber Wahana Musi. The research method is quantitative, i.e., descriptive and verification. The data gained from distributing questionnaires are considered primary data. The research variables are exogenous variables of compensation and working environment and endogenous variables of organizational commitment and employee performance. Data analysis techniques are descriptive statistical analysis and structural equation modeling analysis, based on AMOS. The findings of this study are that there is a positive and significant effect of compensation on organizational commitment; there is a negative and insignificant effect of the working environment on organizational commitment; there is a positive and significant effect of compensation and the working environment simultaneously on organizational commitment; and there is a positive and significant effect of compensation on performance; there is a negative and insignificant effect of the working environment on performance; there is a positive and insignificant effect of organizational commitment on performance; and there is a positive and significant effect of compensation, working environment, and organizational commitment simultaneously on performance